Effectiveness of ICT-integrated pedagogy on pre-service teachers’ teaching competence in mathematics - Samantray, Ashapurna; Behera, Rashmi Ranjan; Acharya, Amulya Kumar (Frontiers in Education, 2024)
The influence of teachers’ teaching competence on students’ academic performance is pivotal, prompting an examination of the efficacy of ICT-integrated pedagogy in enhancing the teaching competence of pre-service mathematics teachers. This quasi-experimental research employed a pre-test, and post-test control group design involving 30 pre-service teachers, with 15 participants assigned to both the experimental and control groups. Throughout a four-week duration, the experimental group received instruction utilizing ‘ICT-integrated pedagogy,’ while the control group was taught applying traditional ‘Lecture-based pedagogy.’ Employing a ‘Mathematics Teaching Competence Scale,’ both cohorts were assessed prior to and following the intervention, with data subjected to analysis using descriptive statistics and t-tests in SPSS version 20. The results revealed that pre-service teachers in the experimental group, exposed to ‘ICT-integrated pedagogy,’ demonstrated superior mathematics teaching competency compared to their counterparts in the control group. These findings advocate for the positive impact of ICT-integrated pedagogical approaches in nurturing the teaching proficiency of pre-service teachers. Consequently, this study suggests the widespread implementation of this approach by Teacher Educators, envisioning its potential to engender competent and high-quality teachers.